Applying the technology acceptance model to investigate intention to use of the learning management system post COVID 19 pandemic the case of UP Visayas College of Management undergraduate students - De los Santos, April Joy.; Hidrosollo, Isabella; Muellenero, Jay-an.; Sorillo, Gladys (2022.)
academic institutions utilized Learning Management Systems (LMS) during the Covid-19 pandemic for online model of learning. Resumption of face-to-face classes in gradually being administered by some universities, so continuing or ceasing the use of LMS can be a preposition. This study aims to study the factors that affect undergraduate students' intention to use the Learning management System of UP Visayas. A quantitative correlational research design was used and paterned the theoretical framework with the Technology Acceptance Model (TAM). The relationship of the external variables being studied in this paper are System Quality (SQ), Computer Self-Efficacy (CSE), and Internet Connectivity Experience (ICE) towards Perceived Ease of Use (PEOU) and Perceived Usefulness (PU of the UPV Learning Management System (LMS). The respondents of this study are the undergraduate students of UPV College of Management. The constraints in data collection due to remote learning led to collecting of primary data through an online survey. The survey was administered through Google Forms with the questionnaire containing 36 questions in the form of Likert Scale. A reliability test using Cronbach alpha was conducted to ensure that the scale of items in the questionnaire are consistent and spearman who was used for the statistical test of correlation, which measures relationship between variables. Results showed that the variables SQ and CSE have a positive relationship with PU and PEOU while ICE with PU and PEOU did not. The study also revealed a positive relationship between PEOU and PU, PEOU and PU towards BI, and BI and Actual system use. The study also probed that students consider using the LMS pst pandemic. Findings of this research have implications in the design and implementation of LMS.
Undergraduate Thesis (Bachelor of Science in Business Administration-Marketing). -- Iloilo City : University of the Philippines Visayas - College of Management, July 2022.